Optimal Placement of Phasor Measurement Units using k-PowerDomination Number in Grid Networks (European Journal of Pure and Applied Mathematics, 2025)
The problem of monitoring an electric power system by placing Phasor Measurement Units in the system as possible is closely related to the well-known power domination problem in graphs. In this paper, we compute, 2-power domination number for fully connected cubic networks and also developed k-power domination algorithm for specific networks and evaluates its performance across these networks. Furthermore, the algorithm’s outputs are used for various other applications such as fault detection and localization, state identification, accuracy improvement, and cyber security enhancement, thereby making it a valuable tool for utilities and grid operators.
Keywords: Optimal PMUs Placement; Dominating Set; Facility Location Problem